Knowledge Sharing and Co-Creation: the UPOU’s Master of Public Management Program’s Innovation on Quality Assurance for ODeL - Gervacio, Juvy Lizette M.; Cruz, Larry N.; delos Reyes, Joana Marie S. (International Journal on Open and Distance e-Learning, 2018)
Development in information and communications technology (ICT) has brought in new strategies and innovations to improve the quality of online courses and online teaching and learning. Further, it has enhanced institutional networking and collaboration and provided more opportunities for knowledge sharing and co-creation. This paper presents the innovation of the Master of Public Management (MPM) Program of the University of the Philippines Open University (UPOU) on quality assurance through learning visit/externship of MPM faculty members. Specifically, the paper a) discusses knowledge sharing and co-creation innovation for online resources; b) identifies the institutions where the MPM program has collaborated with; c) discusses the output of the innovation in relation to quality assurance; and d) identifies the challenges and prospects of the strategy.